Perancangan Media Pembelajaran Animasi Untuk Mata Pelajaran “Pemrograman Web” Pada Materi “Pengenalan Html” - Kevin Albryant Bobby Vilalba; Adriyanto Juliastomo Gundo (Jurnal Ilmiah Wahana Pendidikan, 2022)
Web programming is fairly complicated subject to understand. Therefore, a new solution is needed to undestand this learning. So a solution was found. Namely using animation as a learning medium and using Microsoft Power Point to make it.Research and Development (R&D) model from Borg and Gall is used for this study.Questionairre is used as an instrument and assessed by validator. With validator namely material expert, media expert and students. The result obtained were 87.50%, 83.93% dan 87.28%. The conclusion is the animation is categorized as “Good” or “Valid” and suitable for use in learning.